PENGARUH KUALITAS PRODUK, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA ABLE COFFEE AND STORE SEMARANG - Hadi Perdana Gumilang, 12.05.51.0156 (Students Journal of Economic and Management, 2016)
Consumer behavior is all the activities, actions, as well as the psychological processes that drive those actions in the moments before buy, when to buy, use, spend your products and services after doing the above matters or activities evaluated. The purpose of this study was to determine and analyze the influence of the quality of products, promotions, and pricing on purchasing decisions in coffee and store-able. The sampling technique in this study using purposive sampling method with the number of respondents as many as 100 people. The data were analyzed using validity by comparing the value of r count to r tables and reliability tests with Cronbach alpha. Further tested by regression analysis. The results of the research are: (1) The product of quality has positive influence on purchase decisions. (2) Promotion of positive influence on purchase decisions. (3) Prices positive influence on purchasing decisions. Keywords: Quality of Product, Promotion, Price and Purchasing Decisions